SOSIALISASI POLITIK BAGI PEMILIH PEMULA MENJELANG PEMILIHAN UMUM SERENTAK TAHUN 2024 DI KABUPATEN MUSI BANYUASIN PROVINSI SUMATERA SELATAN - Rizky Agustian; Riyan Jaelani (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2024)
This study examines the political socialization efforts conducted by the General Election Commission (KPU) of Musi Banyuasin Regency towards first-time voters leading up to the simultaneous general elections in 2024 in South Sumatra Province, Indonesia. First-time voters are Indonesian citizens who are using their voting rights for the first time in an election. The KPU of Musi Banyuasin plays a crucial role in providing these voters with understanding of the correct voting process. The study adopts a descriptive qualitative approach, employing data collection techniques such as interviews and documentation. Findings indicate that the KPU of Musi Banyuasin has implemented intensive political socialization efforts to prepare first-time voters for the upcoming elections. These efforts involve adjusting the content delivered to ensure its relevance and comprehensibility to the target audience. Political socialization agents from the KPU require not only effective communication skills but also expertise in delivering information clearly and inspiringly. The interaction between these agents and first-time voters is crucial in shaping positive political attitudes and understanding. Keywords : Political Socialization, General Election Commission, First-time Voters